Simulation the Fertility Parameters of Artificial Soils for Green Zones in the Infrastructure of Cities in Western Siberia - EREMIN, Dmitry I.; EREMINA, Diana V. (Journal of Environmental Management and Tourism; Vol 9 No 3 (2018): JEMT Volume IX Issue 3(27) Summer 2018DO - 10.14505//jemt.9.3(27).20, 2018)
A method is proposed for creating artificial potting soils on the basis of modeling optimal physical properties for the growth and development of lawn grasses and flower beds in the cities of Western Siberia. The properties of soils obtained by mixing the corresponding components with the specified characteristics of the granulometric composition and the main water-mechanical properties are studied. The work is based on regression formulas that are part of the mathematical model of fertility of artificial soils. When creating a fertile layer, any local materials (clay, sand, peat) can be used as components, which reduce the cost of transportation and storage of imported raw materials. The resulting soil is capable of ensuring the long-term growth of herbs and flowers in the conditions of urban development and the severe Siberian climate.